2022
DOI: 10.1039/d2gc02656b
|View full text |Cite
|
Sign up to set email alerts
|

Deep eutectic solvents as a stabilising medium for NAD coenzyme: unravelling the mechanism behind coenzyme stabilisation effect

Abstract: Nicotinamide adenine dinucleotide (NAD) coenzyme is a vital part of numerous enzymatic reactions that are involved in all major biological processes from energy metabolism to cell survival. Accordingly, it is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…This was followed by the TD-DFT computations at the same level of theory considering 32 lowest singlet electronic excitations. The choice of this setup was prompted by its recent success in modeling UV/Vis spectra of organic and inorganic systems in various solvents [41][42][43].…”
Section: Computational Detailsmentioning
confidence: 99%
“…This was followed by the TD-DFT computations at the same level of theory considering 32 lowest singlet electronic excitations. The choice of this setup was prompted by its recent success in modeling UV/Vis spectra of organic and inorganic systems in various solvents [41][42][43].…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the case of using DESs for biocatalytic purposes, DESs can offer special benefits. For example, the molecular interactions can be established between DESs and biocatalysts/cofactors, providing stabilization effects on them [58]. Using DESs can sometimes boost reaction efficiency, while the selectivity of biocatalysts can also be enhanced/modified due to a well-organized 3D-network [59].…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, a number of biotranformations have been developed using immobilized whole cells or enzymes, which are outlined in detail in the following sections. Moreover, it was revealed that some DESs even displayed stabilizing effects on nicotinamide cofactors compared to aqueous media, which lays another solid basis for applying cofactor-dependent oxidoreductases in DESs [58]. In addition, to optimize the biocatalytic processes in DESs, the DES-related physicochemical parameters such as dynamic viscosity [80], compound solubility [85][86][87], dynamic water activity [39], and oxygen transfer rates (OTRs) [71] were investigated comprehensively via experiments and computational analysis.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most useful property of NADES solvents is their tunability, meaning that numerous combinations of HBA and HBD in different ratios can be designed, giving the opportunity for rational solvent design to meet specific aims [22,23]. In this regard, the ratios between HBA and HBD components has been found to affect both the activity and stability of different class of enzymes [24,25].…”
Section: Introductionmentioning
confidence: 99%